Drug Susceptibility and Molecular Epidemiology of Klebsiella pneumoniae Bloodstream Infection in ICU Patients in Shanghai, China - Xiao, Shuzhen; Chen, Tianchi; Wang, Hairu; Zeng, Qian; Chen, Qing; Yang, Zhitao; Han, Lizhong; Chen, Erzhen (Frontiers in Medicine, 2021)
Background: Bloodstream infections (BSIs) are recognized as an important nosocomial infections. Klebsiella pneumoniae is one of the major causes of bacteremia. This retrospective study focused on drug susceptibility and molecular epidemiology of K. pneumoniae isolated from ICU patients with BSI in Shanghai, China. Methods: Consecutive K. pneumoniae isolates were collected from ICU patients. Antibiotic susceptibility testing was conducted by broth microdilution method. PCR was performed to detect antimicrobial resistance genes. We also completed multilocus sequence typing (MLST) and GoeBURST was used to analyze the result of MLST. Results: A total of 78 K. pneumoniae isolates were enrolled. K. pneumoniae from ICU bloodstream infections (ICU-BSIs) were highly resistant to almost all common antibiotics. The most frequent resistance determinants responsible for extended-spectrum β-lactamase (ESBL) producers were blaCTX-M-14, blaCTX-M-15 and blaCTX-M-55. KPC was the only enzyme, which was detected by the carbapenemase producers. The most principal sequence types (STs) were ST11, ST15 and ST23. Conclusions: This study presents for the first time the antibiotic resistance phenotype and molecular epidemiology of K. pneumoniae isolated from ICU patients with bloodstream infections in Shanghai. ICU-BSI K. pneumoniae is characteristic of high resistance rate. The occurrence of KPC-2 enzyme may result from nosocomial clonal dissemination of ST11 K. pneumoniae.